Trophic ecology of large pelagic fish in the Saint Peter and Saint Paul Archipelago, Brazil - Albuquerque, F. V.; Navia, A. F.; Vaske, T. [UNESP]; Crespo, O.; Hazin, F. H.V. (CSIRO Publishing, 2019)
Trophic relationships of large pelagic predators can determine the structure and dynamics of oceanic food webs. The feeding habits and trophic ecology of five large pelagic fish (Acanthocybium solandri, Coryphaena hippurus, Elagatis bipinnulata, Thunnus albacares and Thunnus atlanticus) in the Saint Peter and Saint Paul Archipelago were evaluated to determine whether there is a trophic-niche overlap or resource partitioning among them. Eighty prey items found in 1528 stomachs were identified and grouped into Cephalopoda, Cnidaria, Crustacea, Gastropoda, Teleostei and Tunicata. Exocoetidae and Scombridae were the main prey in the diet of Acanthocybium solandri. In C. hippurus, Cheilopogon cyanopterus and Exocoetus volitans were the most important prey items, whereas C. cyanopterus was the main prey for T. albacares. Thunnus atlanticus consumed a great proportion of invertebrate species, with shrimps of Sergestidae family being particularly important. The gastropod Cavolinia sp. was the most important prey for E. bipinnulata. The five species had a high trophic specialisation and a high trophic level (>4.4), whereas most dietary overlaps were consistently low. The most important factor for diet dissimilarity was the consumption of Exocoetidade. All species were classified as top predators with varied diets, indicating their structural and functional importance in the food web of the Archipelago.
Keywords: diet; feeding ecology; niche overlap; trophic level